Ensuring security at transport and tourism facilities - Sayfutdinov Shukhratjon Sultonovich, (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, security problems in the provision of transport services around the world are analyzed. In addition, the transport industry and opportunities of Uzbekistan are deeply assessed, and proposals are made to increase frustration in transport services.